Control your mind, make affordance available - Jin, Zheng; Lee, Yang; Zhu, Jin (Frontiers in Psychology, 2015)
Evaluating the affordance–control interpretation of the relationship between performance and object estimation has been proposed by psychophysical and psychonomic studies. This study examined the weight estimation–performance relationship. Individuals with visual impairment or blindness put shots that varied in weight among five scales. In Experiment 1, only the perceived weight was a significant performance constraint. In Experiment 2, the weight was perceived as heavier when the participants’ actions were manipulated through cognitive interpretation. The increase in perceived weight appeared to be related to performance and intrinsically scaled to the action, even when the action was only mental rather than physical. The study’s findings suggest that bodily experience and action are the basis for physical judgments and likely underlie other basic cognitive interpretations of sensory stimuli. This suggestion goes hand in hand with the biofunctional approaches which assume direct experience of the integrated wholeness of one's body is fundamental for developing other kinds of awareness. Different perspectives from oriental philosophy and psychology are also discussed.